2015
DOI: 10.1002/acr.22615
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Medial Meniscal Extrusion and Cartilage Loss in Specific Femorotibial Subregions: Data From the Osteoarthritis Initiative

Abstract: Objective Medial meniscal extrusion is known to be related to structural progression of knee OA. However, it is unclear whether medial meniscal extrusion is more strongly associated with cartilage loss in certain medial femorotibial subregions than to others. Methods Segmentation of the medial tibial and femoral cartilage (baseline; 1-year follow-up) and the medial meniscus (baseline) was performed in 60 participants with frequent knee pain (age 61.3±9.2y, BMI 31.3±3.9 kg/m2) and with unilateral medial radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 39 publications
5
37
0
1
Order By: Relevance
“…The coronal MPR DESS sequence was preferred over the IW TSE because of the lower slice thickness (1.5 mm vs 3 mm). The coronal MPR DESS was reconstructed from the near-isotropic sagittal DESS gradient echo datasets, but it has been previously shown to provide a comparable sensitivity to change as the sagittal DESS or coronal FLASH sequence for cartilage analyses 18 and has also been previously used for 3D meniscus analyses 11,19,32 . The use of non-isotropic reconstructed gradient echo datasets is another potential limitation of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…The coronal MPR DESS sequence was preferred over the IW TSE because of the lower slice thickness (1.5 mm vs 3 mm). The coronal MPR DESS was reconstructed from the near-isotropic sagittal DESS gradient echo datasets, but it has been previously shown to provide a comparable sensitivity to change as the sagittal DESS or coronal FLASH sequence for cartilage analyses 18 and has also been previously used for 3D meniscus analyses 11,19,32 . The use of non-isotropic reconstructed gradient echo datasets is another potential limitation of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of other prognostic factors in the knee, medial meniscal damage and extrusion on MRI were associated with cartilage loss over a period of 12e30 months 68,69 , whereas BMLs and synovitis rather surprisingly were not. In women with KOA, the infrapatellar fat pad (IPFP) maximal area appeared to have a negative association with knee symptoms and development of cartilage damage 70 and larger IPFP volumes seem positively associated with knee cartilage volume and concomitant reduction in structural abnormalities on CR and MRI 71 (Fig.…”
Section: Prognosis/predictive Valuementioning
confidence: 94%
“…As meniscal root tears disrupt the circumferential fibers that provide hoop strength, meniscal extrusion with altered biomechanical properties of the meniscus is a critical clinical consequence 1719 . Importantly, recent studies have shown that meniscal extrusion may be closely associated with progressive cartilage loss and accelerated OA 20 . Furthermore, meniscal cysts may occur in both the lateral and medial sides.…”
Section: Principles Of Meniscal Repairmentioning
confidence: 99%